Viral Marketing, Bandwagon Effect dan Keputusan Pembelian: Integrasi Mekanisme Pemediasian Perilaku Konsumtif - Nikken Nur Fanydia Ningsih; Nur Laili Fikriah (Fakultas Ekonomi, UIN Maliki Malang, 2023)
The utilization of TikTok as a digital promotional media is more preferred by marketers today because it is considered more effective in reaching a wider and more efficient target market at a lower cost for promoting products. Based on data, most TikTok user in Indonesia are from the Generation Z demographic. The purpose of this research is to examine the influence of viral marketing and the bandwagon effect on the purchasing decisions of Generation Z on the TikTok Shop, mediated by consumer behavior as an intervening variable. This research is a quantitative study. The data analysis method used in this study is partial least squares using SmartPLS 0.4. The research sample consists of 156 respondents from Generation Z who are TikTok users in Malang. The results of this study reveal that viral marketing, the bandwagon effect, and consumer behavior have a positive and significant impact on purchasing decisions. The consumer behavior variable is able to mediate the influence of viral marketing and the bandwagon effect on purchasing decisions made by the Generation Z demographic in the city of Malang.